2012
DOI: 10.1073/pnas.1211508109
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic ring–ring stacking drives the circadian oscillator clockwise

Abstract: The oscillator of the circadian clock of cyanobacteria is composed of three proteins, KaiA, KaiB, and KaiC, which together generate a selfsustained ∼24-h rhythm of phosphorylation of KaiC. The mechanism propelling this oscillator has remained elusive, however. We show that stacking interactions between the CI and CII rings of KaiC drive the transition from the phosphorylation-specific KaiC-KaiA interaction to the dephosphorylation-specific KaiC-KaiB interaction. We have identified the KaiB-binding site, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
163
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(172 citation statements)
references
References 40 publications
9
163
0
Order By: Relevance
“…were assessed on the isolated CI and CII domains and by negative-stain EM analysis of nanogold-labeled KaiCB (27,32,34,35). However, it was recently reported that KaiB does not interact with the isolated CII domain of KaiC, but interacts with an engineered monomeric form of the CI domain instead (36). It was suggested in this study that CI-CII stacking interactions wedge the CI domains apart, exposing the putative KaiB binding site.…”
Section: Significancementioning
confidence: 84%
“…were assessed on the isolated CI and CII domains and by negative-stain EM analysis of nanogold-labeled KaiCB (27,32,34,35). However, it was recently reported that KaiB does not interact with the isolated CII domain of KaiC, but interacts with an engineered monomeric form of the CI domain instead (36). It was suggested in this study that CI-CII stacking interactions wedge the CI domains apart, exposing the putative KaiB binding site.…”
Section: Significancementioning
confidence: 84%
“…1 B and C), suggesting that CII is necessary not only for retaining ADP on itself but also for regulating the nucleotide-bound state of CI. A recent study showed that the KaiB-KaiC interaction is mediated by the CI domain and that the binding of ADP to CI is necessary for KaiC's association with KaiB (22). Previously, we and another group reported that the phosphorylation of S431 promotes the KaiB-KaiC interaction (16,17).…”
Section: Discussionmentioning
confidence: 97%
“…(i) The autophosphorylation sites are located at subunit interfaces of CII, and each site faces the ATP molecule on the neighboring subunit (14). (ii) KaiA acts on the CII domain to promote autophosphorylation and ATP hydrolysis (20)(21)(22), whereas KaiA has little effect on ATPase activity in the CI domain (22). (iii) ATP accounted for more than 95% of nucleotides bound to KaiC-CI, regardless of the presence or absence of KaiA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations